Assessing the clinical benefit, safety, and patient-reported outcomes with the use of the PAHcare™ digital platform in pulmonary arterial hypertension: a pilot study - Peñate, Gregorio Pérez; Parra, Nuria Ochoa; Morera, Juan Antonio Domingo; Meñaca, Amaya Martínez; Ramón, Marta López; Menéndez, Sergio Cadenas; Marrero, Fernando León; de la Cal, Sara Gómara; Ghadban-Garrido, Cristina; Tolosana, Patricia Royo; Puentes, Javier Martín; Aguayo, Rebeca Aldonza; et al. (Frontiers in Public Health, 2024)
Introduction 45 Digital health interventions, particularly mobile health platforms, have shown promise in supporting 46 patients with respiratory conditions, but their application in pulmonary arterial hypertension (PAH) 47 remains limited. We aimed to assess the feasibility, acceptability, and potential clinical benefit of the 48 novel PAHcare™ digital platform as a patient-centred intervention for PAH management through a 49 prospective, single-arm, multicenter pilot study conducted on 53 patients diagnosed with PAH who 50 used the platform for six months. 51 Methods 52 The primary objective was to assess the impact on Health-Related Quality of Life (HRQoL) through 53 questionnaires. Secondary objectives included evaluating clinical outcomes, including disease 54 progression, PAH signs and symptoms, the 6-minute walking test, and the patient's symptom 55 perception. Additionally, we assessed patient satisfaction and engagement with the PAHcare™ 56 platform, interaction with health coaches, retention, costs and healthcare resource utilisation 57 (HCRU), and safety through monitoring device incidents. 58 Results 59Minimal changes in HRQoL and clinical outcomes were observed over six months. A noteworthy 60 92.4% of patients actively used the platform in the first month, maintaining high usage throughout 61 the study. Patient satisfaction was substantial, with more than half of the patients expressing 62 excellence in service quality, willingness to reuse the platform, and fulfilment of their needs. Health 63 coach interaction was high, with 76% of patients initiating contact within the first week. User 64 retention rates were 70%, with prevalent ongoing usage and interaction with healthcare professionals 65 even after the study. In terms of HCRU and costs, the study showed no significant changes in PAH-66 related hospital admissions, clinical visits, or tests. Finally, the low number of device-related 67 incidents indicated platform safety. 68This pilot study provides compelling evidence supporting the feasibility and acceptability of the 70 PAHcare™ digital platform to empower patients to manage their disease and significantly enhance 71 their overall experience with PAH. 72